Pengaruh Perputaran Modal Kerja dan Perputaran Piutang terhadap Profitabilitas pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI - Nurhaliza Putri Sahabuddin; Fajriani Azis; Samsinar Samsinar (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to examine the effect of working capital turnover and accounts receivable turnover on profitability, both partially and simultaneously, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The independent variables used are working capital turnover (X1) and accounts receivable turnover (X2), while the dependent variable is profitability (Y). The research population consists of 23 food and beverage sub-sector companies listed during the period. The sample was selected using purposive sampling, consisting of 15 companies observed over three years, resulting in 45 research samples. Data were collected through documentation techniques. The partial test results (t-test) indicate that working capital turnover has a coefficient of 0.166 with a significance level of 0.025, showing a positive and significant effect on profitability. Accounts receivable turnover has a coefficient of 0.729 with a significance value of less than 0.001, also indicating a positive and significant effect on profitability. The simultaneous test results (F-test) show a significance value of 0.001, meaning that both independent variables jointly have a significant effect on profitability. The coefficient of determination (R²) shows that these two variables explain 55.7% of the variation in profitability, while the remaining portion is influenced by other variables outside the research model.